La mustia hilachosa del frijol - Mora B., B.; Gálvez E., Guillermo E. (International Center for Tropical Agriculture, 1987)
The etiology and epidemiology of web blight of beans (Thanatephorus cucumeris) are reviewed and its control through cultural practices, use of tolerant cv. and fungicides is discussed. Cultural practices that have proved effective in controlling the disease include use of pathogen-free seed, elimination of crop residues, crop rotation with nonhost species (grasses and some vegetables), use of soil mulches, and intercropping. Tolerant cv. are Turrialba 1, Porrillo 70, Porrillo Sintetico, S 630 B, Talamanca, Negro Huasteco 81, and Huetar; bean lines that have shown intermediate resistance are BAT 76, XAN 112, BAT 450, HT 7719, and ICTA 883-2-M. Chemical control has been effective with, for example, benomyl (0.25-0.30 kg/ha), triphenyltin hydroxide (0.4 kg/ha), triphenyltin acetate (0.16 kg/ha), carbendazim (0.3 kg/ha), captafol (1 kg/ha), NF 44 (0.5 kg/ha), and thiabendazole (0.25 kg/ha). The disease should be managed using an integrated approach in which bean cv. with intermediate resistance are combined with cultural practices aimed at reducing the incidence of primary and secondary inoculum and a min. application of fungicides. (CIAT)